Collaborating and Sharing RPL Knowledge and Practice: The Case of the RPL Digital Badge in Ireland (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The concept of the balance of power in education emphasizes the importance of collaborative and inclusive approaches, where multiple stakeholders work together to create a more effective and equitable educational environment (Marginson & Considine, 2000; Kristenson et al., 2023). RPL, the Recognition of Prior Learning, was given a statutory footing in Ireland in 2012 through the Quality and Qualifications (Education and Training) Act and is evidenced in the Access, Transfer and Progression policy (2015). Within Irish higher education, 3,807 individuals utilized RPL in 2022/2023 as a means to gain access, advanced entry or credit/module exemption(Recognition of Prior Learning (RPL), 2024).  While progress has been made, RPL remains on the periphery as a means of access to and progression through higher education. Staff capacity building by collaborating and sharing RPL knowledge and practice is one mechanism of moving RPL towards a mainstream activity.   This paper explains how the National Forum for the Enhancement of Teaching & Learning in Higher Education (NFETL) RPL Digital Badge has empowered Irish higher education stakeholders to collaborate and share their RPL knowledge and practice. Over 300 individuals completed the Digital Badge across three deliveries in 2023 and 2024 including47 individuals also completing the RPL Facilitator Badge, which requiresan additional10 learner effort hoursthat participants can take in addition to the Introductory Badge. Those who obtain the Facilitator Badge can then roll out the Introductory and Facilitator Badges at their own institution.Qualitative feedback from participants in these trainings highlights increased staff awareness, confidence, and engagement with RPL. This paper explores the value of these collaborations and how they enhance the capacity of higher education institutions to extend and broaden the implementation of RPL processes and practices that further support a more equitable educational environment.